What is cultural history? - Burke, Peter 1937- (Cambridge, United Kingdom Polity, 2019)
"What is Cultural History? has established itself as an essential guide to what cultural historians do and how they do it. Now fully updated in its third edition, leading historian Peter Burke offers afresh his accessible guide to the past, present and future of cultural history across the globe"--Provided by publisher.
The great tradition -- Problems of cultural history -- The moment of historical anthropology -- A new paradigm? -- From representation to construction -- Beyond the cultural turn? -- Cultural history in the twenty-first century.
Includes bibliographical references and index.
Keywords: History -- Methodology; History -- Philosophy; Culture -- History